ANALISIS EFEKTIVITAS PENGENDALIAN BIAYA FOOD AND BEVERAGE DEPARTEMENT PADA MAX ONE VIVO HOTEL PALEMBANG - Kusminaini Armin (JURNAL KOMPETITIF, 2016)
The purpose of this study was to Know the Cost Effectiveness of Control of Food and Beverage department At Max One vivo Hotel Palembang .. By the way do Food and Beverage Cost Control department At Hotel Max One Vivo Palembang .. the issues raised in this research is how the effectiveness of cost control Food and Beverage at the Hotel Max One Vivo Palembang. This study basically discusses Accounting Management or Food and Beverage Cost Control Department, the Cost Control Effectiveness as a basis for preparing the budget. From the discussion conducted, turns in cost control is still not optimal and budgetary priority in the history refer not realized in the previous year, so that the results obtained did not show improvement. Besides, the cost control is not maximized because of coordination and control is not yet optimal. Seeing these conditions it is recommended that the determination of the budget must be in accordance with the results achieved previously, and the improvement of coordination and control in the food and beverage department of Max One Hotel Vivo Palembang thereby increasing the effectiveness of cost control. Keywords: Cost Control Effectiveness